Meeting report - building a centrosome - Baffet, Alexandre D.; Martin, Carol-Anne; Scarfone, Ilaria; Daly, Owen M.; David, Ahuvit; Tibelius, Alexandra; Lattao, Ramona; Hussain, Muhammad S.; Woodruff, Jeffrey B. (Journal of cell science, 2013)
Skip to Next Section - Located in the 16th century Wiston House in West Sussex, UK, the ‘Building a Centrosome’ Workshop was organised by The Company of Biologists and chaired by Fanni Gergely and David Glover (University of Cambridge). Held in March 2013, the Workshop gathered together many of the leaders in the field of centrosome biology, as well as postdocs and students who were given the opportunity to meet and interact with many of the scientists who inspired their early careers. The diverse range of speakers provided a multi-disciplinary forum for the exchange of ideas, and gave fresh impetus to tackling outstanding questions related to centrosome biology. Here, we provide an overview of the meeting and highlight the main themes that were discussed.
Gesehen am 05.11.2020